2022
DOI: 10.1088/1361-6668/ac9559
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of transverse compressive loads on the electromagnetic performance of superconducting CORC® cables

Abstract: High-temperature superconductor (Re)Ba2Cu3Ox (ReBCO) conductor on round core cable (CORC®) has a large current carrying capacity for high field magnets. Lorentz forces acting on CORC conductors, cause a reduction of the critical current, or even permanent degradation of their performance when exceeding critical values. Transverse compressive stress is one of the principal mechanical stresses when CORC cables are bundled to CICC conductors capable of operating at currents up to 100 kA in magnetic fields of up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 48 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…The first study of this performance is carried out by Van Der Laan et al and it is found that parameters such as the former size, the gap between HTS tpaes, and the thickness of copper laminating of the tape have a significant effect on the transverse compression performance of CORC cables [31]. Yan et al found that the winding angle of HTS tape also has a significant impact on the transverse compression performance of CORC cables [32]. Whereas, the current research on the transverse compression performance of CORC cables is not comprehensive enough, and the influence of many factors on the transverse compression performance of CORC cables is still blank.…”
Section: Introductionmentioning
confidence: 99%
“…The first study of this performance is carried out by Van Der Laan et al and it is found that parameters such as the former size, the gap between HTS tpaes, and the thickness of copper laminating of the tape have a significant effect on the transverse compression performance of CORC cables [31]. Yan et al found that the winding angle of HTS tape also has a significant impact on the transverse compression performance of CORC cables [32]. Whereas, the current research on the transverse compression performance of CORC cables is not comprehensive enough, and the influence of many factors on the transverse compression performance of CORC cables is still blank.…”
Section: Introductionmentioning
confidence: 99%
“…In [8] a detailed parametric analysis, validated through experiments, aimed at defining the stress-strain state for the determination of the critical strain that may cause the breakage of the YBCO layer, considering the bending of the cable. In [21] and in [22], electromechanical simulation, based on T −A formulation, were performed to predict the strain state and the critical current degradation for straight CORC ® cables. The thermal behavior was not considered in those models and the current was imposed without any possibility of redistributing, if necessary, due to uneven strain in different tapes.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments show that REBCO cables are capable of maintaining high current-carrying capability under a high electromagnetic (EM) load [23]. However, the mechanical performance of the conductor on round core (CORC) cables is associated with the tape specifications [24], winding parameters [25], screening current [26] and so on. Moreover, degradation was caused by the deformation of the cables during bending and EM cycling in modeling and experimental tests [27,28].…”
Section: Introductionmentioning
confidence: 99%